Detecting changes in postural sway. (23rd June 2020) - Miyashita, Theresa L.; Cote, Christopher; Terrone, Douglas; Diakogeorgiou, Eleni
Abstract: Postural sway has been identified as a valid marker for assessing the presence of a concussion and monitoring return to activity progression. Instrumented balance assessments have shown to be more reliable in detecting postural sway. However, many sports medicine programs cannot afford to purchase a force plate system to objectively assess postural sway and changes, which may occur due to a head injury. The purpose of this study was to determine if the C3Logix™ application can detect postural sway with the same degree of accuracy as the VSR Sport™ by NeuroCom®. Forty-five Division I Lacrosse players, consisting of 27 males and 18 females, participated in this study. Participants completed the Stability Evaluation Test (SET) on the VSR Sport™ while simultaneously completing the same balance assessment via the C3Logix™ application. The balance assessment consisted of three stances (double leg, single leg, tandem stance) on two surfaces (firm & foam) for a total of six trials. A Pearson correlation was used to determine the correlation between the postural sway velocity values from the VSR Sport™ and ellipse volume values from the C3Logix™ application. Each of the stances on both the firm and foam surface was found to have a strong correlation, suggesting the C3Logix™ application is a valid alternative to postural assessments on a force plate.